2020
DOI: 10.3390/atmos11080777
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Orographic Rain Drop-Size Distribution at Cherrapunji, Northeast India

Abstract: The rain drop size distribution (DSD) at Cherrapunji, Northeast India was observed by a laser optical disdrometer Parsivel 2 from May to October 2017; this town is known for the world’s heaviest orographic rainfall recorded. The disdrometer showed a 30% underestimation of the rainfall amount, compared with a collocated rain gauge. The observed DSD had a number of drops with a mean normalized intercept log 10 N w > 4.0 for all rain rate categories, ranging from <5 to >80 mm h −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Conversely, Mawsynram is situated on the opposite side of the hills, experiencing the rain shadow effect. This phenomenon causes the descending air to warm, leading to reduced rainfall in Cherrapunji compared to Mawsynram [63].…”
Section: Figure 2 Conceptual Model Of the Airflow And Microphysics Of...mentioning
confidence: 99%
“…Conversely, Mawsynram is situated on the opposite side of the hills, experiencing the rain shadow effect. This phenomenon causes the descending air to warm, leading to reduced rainfall in Cherrapunji compared to Mawsynram [63].…”
Section: Figure 2 Conceptual Model Of the Airflow And Microphysics Of...mentioning
confidence: 99%
“…Alternatively, we can derive a and b using the local rain by relating the rainfall rate and attenuation (A) as follows. Using the availability of the rainfall parameters, including the raindrop size distribution measurement from a local disdrometer, we can estimate the PSD based on Equation (1) and the rain-induced attenuation (A) by an integral of all the water drop sizes [39][40][41]:…”
Section: Estimation Of Rain-induced Attenuation Over Millimeter-wave Linksmentioning
confidence: 99%
“…Similar conclusions were reached by Dolan et al [30], who identified two distinct DSD types from global observations, both of which resulted in heavy rainfall characterized by relatively large average raindrop sizes (smaller), the number concentration was relatively low (high), corresponding to warm rain (ice-based) convection. The characteristics of DSD also varied significantly within specific convective systems [31][32][33]. Such complexity of heavy precipitation DSD observations has posed a major challenge to the comprehensive parameterization of microphysics and the accuracy of quantitative precipitation forecasts.…”
Section: Introductionmentioning
confidence: 99%